Influence of continuous phase viscosity on emulsification by ultrasound - Behrend, O; Ax, K; Schubert, H (Ultrasonics sonochemistry, 2000)
Power ultrasound is one means among others of mechanically producing emulsions. In spite of numerous publications on the basic principles of this technique, there is insufficient knowledge of continuous ultrasound emulsification processes and the main parameters of practical relevance. A comparison of this system with other continuous mechanical emulsifying devices is made. The effect of continuous phase viscosity on droplet disruption due to ultrasound is the subject of a more detailed investigation. Continuous phase viscosity is varied by means of water soluble stabilizers (o/w systems) and different oils (w/o systems). At constant energy density, droplet size decreases when adding stabilizers, whereas the viscosity of the oil in w/o emulsions has no effect. Qualitative investigations of the local distribution of cavitation have shown very small penetration depths of cavitation into the liquid. This emphasizes the need for improvement of apparatus design to optimize the emulsification process.